Report - Coventry Trades and Labour Council, 12 May 1926 (Coventry)
1926-05-12 "Report - Coventry Trades and Labour Council, 12 May 1926" [g0382001.jpg], 12 May 1926, Coventry Trades and Labour Council Local Organisation